Effects of blunt force injuries in third-instar Drosophila larvae persist through metamorphosis and reduce adult lifespan. - Lika, J.; Katzenberger, R.J.; Ganetzky, B.; Wassarman, D.A. (microPublication Biology, 2021)
Blunt force injuries are a significant cause of disability and death worldwide. Here, we describe a Drosophila melanogaster model of blunt force injury that can be used to investigate cellular and molecular mechanisms that underlie the short-term and long-term effects of injuries sustained at a juvenile stage of development. Injuries inflicted in late third-instar larvae using the spring-based High-Impact Trauma (HIT) device robustly activated the humoral defense response process of melanization and caused larval and pupal lethality. Additionally, adults that developed from injured larvae had reduced lifespans, indicating that cellular and molecular mechanisms activated by blunt force injuries in larvae persist through metamorphosis and adult development. Previously, the HIT device has been used to investigate genetic and environmental factors underlying mechanisms that contribute to consequences of blunt force injuries incurred in adult flies. This work expands use of the HIT device to a juvenile stage of development, offering the opportunity to investigate whether the consequences of blunt force injuries involve different factors and mechanisms at different stages of development.